PENGARUH CAR, LDR, DAN NPL TERHADAP KINERJA KEUANGAN PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BEI - Hadi, Shilvy Meilinda (Jurnal Mahasiswa Akuntansi Samudra, 2023)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Non Performing Loans (NPL) on banking financial performance as measured by Return On Assets (ROA) in banking sector companies listed on the Indonesia Stock Exchange. . The sample in this study is 10 banking companies listed on the IDX. Methods of data analysis using multiple linear regression analysis, t test, F test, and analysis of the coefficient of determination. From the multiple linear regression analysis, the regression equation Y = 9.033 + 0.016X1 + 0.162X2 – 0.002X3 is obtained. From the t test it is known that the Capital Adequacy Ratio has a significant effect on Return On Assets, where the t sig value is obtained. 0.021 is smaller than 0.05. Loan to Deposit Ratio has a significant effect on Return On Assets, where the t sig value is obtained. 0.000 is less than 0.05. Non Performing Loans have a significant effect on Return On Assets, where the t sig value is obtained. 0.025 is smaller than 0.05. From the F test it is known that the Capital Adequacy Ratio, Loan to Deposit Ratio, and Non-Performing Loans simultaneously have a significant effect on ROA, where a sig F value is obtained. 0.000 is less than 0.05. From the analysis of the coefficient of determination it is known that CAR, LDR, and NPL affect Return On Assets in banking companies listed on the Indonesia Stock Exchange by 70.5%, while the remaining 29.5% is influenced by other variables outside this research model.